Framing as a tool for social mobilization. A frame analysis of Ni una menos movement on Facebook - Ponte Torrel, Juan Manuel (2020)
Lima experienced in August 2016 a massive mobilization against violence against women. From different theoretical approaches (frustration, mobilization of resources, collective action and political opportunity) an attempt was made to explain these events; however, few focused on the framing approach as an instrument of social mobilization. Thus, collective action frameworks are action-oriented sets of beliefs and meanings that inspire and legitimize social movement organizing activities and campaigns. We see that social movements seek to build a discourse through frames, which give them the opportunity to sustain the movement, or, as far as possible, to add a greater number of followers and seek solutions that benefit them. To do this, we start from the question: What frames were the most important in the Facebook managed by the collective “Ni Una Menos Peru: they touch one touch all” during the mobilization processes against violence against women? To answer this question, we took as an object of analysis the Facebook posts of the most important page that the aforementioned movement had. For the capture and analysis of the publications we rely on computational techniques of text analysis, in addition to content analysis. Finally, it is concluded that the frames of justice, violence and gender guided the march of the movement, although each of them presented different stages (diagnosis, prognosis and motivation) to articulate the demands.